Associations Between Child and Adolescent Beverage Intakes and Age 17-year Percent Body Fat (P21-064-19). (13th June 2019) - Marshall, Teresa; Curtis, Alexandra; Cavanaugh, Joseph; Warren, John; Levy, Steven
Abstract: Objectives: Observational studies in children and adolescents suggest that sugar-sweetened beverage (SSB) intakes are a risk factor for obesity, with obesity generally assessed using body mass index. Our objective was to investigate associations between child and adolescent beverage intakes collected longitudinally and % body fat at age 17. Methods: Iowa Fluoride Study/Iowa Bone Development Study participants were recruited at birth and followed longitudinally with detailed questionnaires sent at least every 6 months. Mean daily (area under the curve) beverage intakes of participants ( n  = 174 male, n  = 201 female) were calculated for the age ranges 1.00–3.00, 3.01–5.00, 5.01–9.00, 9.01–11.00, 11.01–13.00, 13.01–15.00, and 15.01–17.00 years from beverage questionnaire-reported intakes of milk, 100% juice, SSBs and water-based sugar-free beverages (WBB). Three-day diaries and food frequency questionnaires were used to calculate mean energy intakes for these age ranges. Percent body fat (%BF) was assessed by dual energy x-ray absorptiometry (DXA) at age 17-year clinic exams. Generalized linear models based on the gamma distribution and a log link function were used to examine associations between the independent variables of beverage intakes (at a specific age range), baseline socioeconomic status (SES), sex, and energy intakes, and the dependent variable %BF at age 17. Results: Adolescent, but not early childhood, milk and 100% juice intakes were negatively associated with mean %BF at age 17. For example, the estimated effect of 8 additional ounces of milk daily at ages 15.01–17.00 years was a 4% decrease in %BF at age 17 (95% CI 6% decrease, 1% decrease), and the estimated effect of 8 ounces of 100% juice was an 11% decrease in %BF (95% CI 18% decrease, 3% decrease). Neither childhood nor adolescent SSB or WBB intakes were meaningfully associated with %BF at age 17. Adjustment for baseline SES, sex and energy intakes had a marginal impact on estimated effects. Conclusions: Adolescent milk and 100% juice, but not SSB or WBB, intakes were associated with lower %BF at age 17. The results suggest that associations between beverage intakes and obesity may depend on how obesity is measured. Funding Sources: National Institutes of Health (R03-DE023784, R01-DE12101, R01-DE09551, UL1-RR024979, UL1-TR000442, UL1-TR001013, M01-RR00059); The Roy J. Carver Charitable Trust; Delta Dental of Iowa Foundation.